Stop the presses! Or wait, we might need them: Firm responses to local newspaper closures and layoffs - Kim, Min; Stice, Derrald; Stice, Han; White, Roger M. (Journal of Corporate Finance, 2021)
Media as a whole has been shown to play an important role as an information source, information intermediary, and monitor of public firms, but much less is known about whether local newspapers play a similar role. We attempt to shed light on this issue, and we investigate if and how firms respond to changes in the local newspaper industry, where closures and layoffs have become the norm. Compared to a sample of matched control firms, we find that following newspaper closures and large industry layoffs, nearby public companies boost dividend payouts. This result follows from prior research suggesting that investors pressure managers to increase dividends in response to growing agency problems. Cross-sectional analyses confirm that our results are driven by geographically-concentrated firms that rely more heavily on local newspapers as a monitor and information source. Our findings suggest that local newspapers play an important role as an information intermediary and monitor of public firms, and that the disappearance of local newspapers exacerbates agency problems in nearby firms that tend to be remedied by higher dividends.